(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
This study focuses on analyzing the spending patterns of youths from across the B40 and M40 income strata living in Kuala Lumpur. To achieve the objectives of this study, an analytical framework was developed that prioritizes needs. These needs include basic necessities, shelter and health, family, religious matters, and free time. The results of this study show that there is no significant difference between the two groups in terms of spending patterns. However, there is a difference in terms of priorities, which are led by the desire to guarantee survival in the city. Basic necessities, such as house ownership, feature as top topics in the discussion of expenditure, especially among lower and middle-income groups. However, the pricing of homes which renders them unattainable to these two groups, especially in the urban setting, results in expenses related to home purchases not being a main item in their spending patterns. This study highlights that the type of residence contributes to the shaping of the lifestyle and spending patterns of urban youth. Keywords: urban, youth, needs, Malay, income, expenditure